ADAPTASI MODEL PENDIDIKAN DI ERA DISRUPTIVE INNOVATION DAN KNOWLEDGE-BASED ECONOMY - Ferdinan, Bernardus Aris (JP (Jurnal Pendidikan) : Teori dan Praktik, 2022)
The era of disruptive innovation and knowledge-based economy has indirectly affected various sectors of human life. In addition, the new era requires every person to be able to adapt to various changes, so they can survive. Therefore, for Indonesia to have a superior workforce in the era of disruptive innovation and knowledge-based economy, an education model is needed that can prepare a superior workforce. An educational model that can help students to deepen their abilities, basic skills, and cross functional skills. An educational model that can prepare students to face challenges in the future. An educational model that can build competitive advantage. In addition to the education model, the important thing in preparing a superior workforce is the role of educators. The articles in this study were obtained through a library study, the results showed that the role of educators is irreplaceable in the world of education. In the new era, educators are required to have irreplaceable roles related to educational competence, Competence for technological commercialization, Competence in globalization, Competence in future strategies, and Competence counselors.